SOME OBSERVATIONS ON THE BIOLOGY OF PENAEUS INDICUS H. MILNE-EDWARDS AND PENAEUS MONODON FABRICIUS FROM THE CHILKA LAKE - Rao, A V Prabhakara (Indian Journal of Fisheries, 2011)
The information available on the biology and fishery of the two commercially important penaeid prawns Penaeus indicus H. Milne-Edwards and Penaeus monodon Fabricius from the Chilka lake is not much. Kemp (1915) gave brief notes on the migratory nature of these two species and described the colouration of the postlarvae of P. monodon. Devasundaram (1954) furnished information on the magnitude of catches of these two species, while Jones and Sujansinghani (1954) gave information on the gear operated for the capture of prawns and the fishing season together with export figures for large and small sized prawns for the period 1948-50. Jhingran et al. (1963) gave the landing figures, period of migration into the sea and period of post-larval recruitment into the lake and Jhingran and Natarajan (1966) furnished brief notes on the lunar periodicity of the catches, rate of growth and food and indicated the existence of at least two broods. Studies on the biology of Penaeus indicus ("Kantala chingri") and Penaeus monodon ("Bagda") were undertaken by the author in the Chilka lake during an eight-month period from May to December 1963. The present preliminary observations are on the length-weight relation, sex ratio, food, moulting, breeding and migration.